DEVELOPMENT OF A PERFORMANCE-BASED INCENTIVE MODEL FOR NATIONAL HIGH SCHOOL MALANG TEACHERS AFTER THE COVID-19 PANDEMIC - Shanti Dri Lestari; Handoko, Fourry; Hutabarat, Julianus (Journal of Sustainable Technology and Applied Science (JSTAS), 2024)
National High School Malang is one of the best private schools with a myriad of achievements. In 2019, National High SchoolMalang was honored as one of Indonesia's best private schools by the Minister of Education and Culture. National High School Malang is one of the private schools in Malang City that has also been affected by the Covid-19 pandemic. The Covid-19 pandemic has not really ended and life must go on. The Covid-19 pandemic has indirectly changed labor patterns both in the scope of government, agencies, private sector, and others. This research aims to design a model for determining the criteria for providing performance-based incentives to teachers at National High SchoolMalang to improve service quality after the Covid-19 pandemic. In this study, the calculation results are used to determine the amount of incentive proposals that will be obtained by each teacher by taking into account the results of the performance assessment. Based on the results of the calculation of the proposed incentives, it can be concluded that there was an increase in the average incentive for each teacher by 35%. This shows that with an increase in incentives it is expected that there will be an increase in the value of work performance. And in line with the results of the calculation of the proposed incentive increase, it was found that there was also an increase in work performance of 51%. With this, it can be concluded that the provision of incentives has a major effect on increasing work performance.